Inferring neuron-neuron communications from single-cell transcriptomics through NeuronChat - Wei Zhao; Kevin G. Johnston; Honglei Ren; Xiangmin Xu; Qing Nie (Nature Communications, 2023)
Neurons communicate differently from non-neuronal cells. Here, authors present a method, NeuronChat, that utilizes scRNA-seq data and/or spatial transcriptomics to infer, visualize and analyze neural-specific cell-cell communication.